MASALANING UMUMIY YECHIMIDAN XUSUSIY YECHIMGA O‘TISH - Zaxidova, M.A.; Giyasova, Z.R. (SCIENCE and SOCIETY, 2022)
In the article explaining the methodology for solving problems of studying the motion of a body moving under the influence of gravity, the ways of transition from the method of finding a general solution to a particular solution are shown and it is shown that the in formativeness of the problem can be increased by applying the method of graphical solution to these types of problems.
Keywords: general solution; partial solution; horizontal; vertical; gravity; body coordinates; maximum height